On the road from environmental biomonitoring to human health aspects: monitoring atmospheric heavy metal deposition by epiphytic/epigeic plants: present status and future needs. (22nd May 2008) - Markert, Bernd; Wuenschmann, Simone; Fraenzle, Stefan; Wappelhorst, Olaf; Weckert, Vera; Breulmann, Gerhard; Djingova, Rumjana; Herpin, Uwe; Lieth, Helmut; Schroder, Winfried; Siewers, Ulrich; Steinnes, Eiliv; et al.
For the past few years, a strong and intensive combined study by analytical scientists and biologists on bioindication and biomonitoring has developed. To achieve a more public-related prophylactic healthcare feature derived from these biotechniques in the future, the collaboration between analytical scientists, ecotoxicologists and especially human toxicologists has to be strongly intensified and promoted. For this purpose, different forms of education and teaching of students on an international level combined with common research projects encompassing the different scientific fields and philosophies are important keys for common success.